STUDY OF IMPROVEMENT IN AGRICULTURAL METHODS THROUGH INNOVATION AND THEIR IMPACT - Bagri, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is an agrarian country where advanced farming methods and innovations are urgently needed. Traditional agricultural practices have limited productivity and adversely affected farmers' incomes. The objective of this research paper is to study the improvements in agricultural methods through innovations and their broader impacts. Special attention has been given to the use of advanced seeds, biotechnology, precision farming, and climate-resilient technologies. Additionally, the effects of these innovations on the environment, farmers' economic conditions, and production capacity have been assessed. The study clearly shows that innovation has increased agricultural production and significantly contributed to raising farmers' incomes while protecting the environment.